THE EFFECT OF LEADERSHIP, WORK ENVIRONMENT, AND DISCIPLINE ON EMPLOYEES’ PRODUCTIVITY AT PT. AMRI MARGATAMA CAPITAL - Setyowati, Rifka .; Lambey, Linda .; Rumokoy, Farlane S. (Universitas Sam Ratulangi, 2017)
Abstract: This research aims to analyze the influence of leadership, work environment, and discipline on employees’ productivity at PT. Amri Margatama Capital. This research is using descriptive quantitative method using multiple regression analysis techniques and use primary data and secondary data in the data from the survey. Data were collected through questionnaires, sample used in this study were 40 respondents. Then carried out methods that includes classical assumption test, hypothesis Ftest and t test, analysis of determination by analysis through SPSS software 22. Ftest and t test were used to analyse simultaneous and partial influence of Leadership, work environment, and discipline on employee productivity. It was revealed from this research that simultaneously influence of Leadership, Work environment, and Discipline was significant on employee productivity at PT. Amri Margatama Capital. But partially, only discipline has a significant influence on employee productivity at PT. Amri Margatama Capital. Based on the results researcher give advice to leaders for enforce discipline in working, and employees must to obey with the rules of work discipline at PT. Amri Margatama Capital.Keywords: leadership, work environment, discipline, productivity